Крылатые панцирные клещи (Oribatei, Galumnoidea) Украины - Гришина, Л.Г.; Сергиенко, Г.Д. (Вестник зоологии, 1978)
In the territory of the Ukrainian SSR 12 mite species of the family Galumnoidea are found, among them two species, Acrogalumna longipluma and Psammogalumna hungarica, are mentioned first for the territory under study. The new subspecies, Pilogalumna allifera montana Grish. et Serg. ssp. n. is described.